A New Technology for Optimized UV-A-Light Energy Transfer to the Cornea in Corneal Crosslinking for Keratoconus - Daxer, Barbara; Ettl, Armin; Daxer, Albert (Journal of Ophthalmic Science, 2024)
Purpose The conventional irradiation technique in corneal crosslinking for keratoconus is characterized by a free irradiation path and parallel light rays directed to the corneal surface. This can cause treatment failures resulting from the steep and irregular corneal curvature as well as from eye and head movement. Here we present a a new and improved irradiation technology for corneal crosslinking (CXL) in keratoconus to avoid such treatment failures. Materials and Methods The presented technology is characterized by a closed irradiation channel which is lined inside with a diffusely reflecting layer and which is mounted to the eye via a suction ring. The effective intensity transferred to a curved photodetector representing the curved cornea of some 7 mm radius was measured for both, the conventional and the new technology. The results were compared with related calculations. Results The UV-A irradiation transferred to a curved cornea of some 7 mm central radius varies across the irradiated area by a factor of 2 for the conventional technology. At a distance of already 2 mm from the vertex the transferred UV-A intensity falls below 2/3 of the central intensity which might affect the effectivity of the treatment. The new technology can keep the intensity transferred to the cornea at a constant level across the entire irradiated area. Conclusion The new irradiation technology can considerably improve the energy transfer to the cornea since the effective intensity at the cornea becomes independent from the corneal shape, the eye movement and the head movement, respectively. This may probably reduce the failure rate of corneal crosslinking in the future.
Keywords: UV-A-light; keratoconus; corneal crosslinking; photographic paper